Evaluation of Wound Dressing Made From Spider Silk Protein Using in a Rabbit Model. (June 2018) - Setooni, Zahra; Mohammadi, Mostafa; Hashemi, Arman; Hashemi, Mohammad; Mozafari, Fateme; Simi, Fateme; Bargahi, Afshar; Daneshi, Adel; Hajiani-E-Asl, Mohammad Reza; Farzadinia, Parviz
The aim of the present article was to study the healing of wounds using spider silk. Eight New Zealand female rabbits were selected as animal model. First, 3 identical wounds with length of 15 mm and a depth of 4 mm on the back of each rabbit were created. The first group, as standard control, did not receive any special treatment, they were treated only with saline and Vaseline locally. The second group, as positive control, received a thin film of phenytoin 1% ointment locally. The third group, as treated group, received a thin film of spider silk protein. At the end of the study, a biopsy of skin was done. After tissue preparation, all sections were evaluated. Some morphometrical parameters such as counting cells, fibroblasts, blood vessels, determination of the area of the wound closure, necrotic tissue, speed of wound healing, and epidermal thickness were done, and for data statistical analysis, SPSS software and Excel software were used. The results of this study showed that spider silk dressing may benefit as a possible effect of nanoparticles in the test preparation in wound healing.